Etiology, severity and treatment outcomes of acute pancreatitis in maharaj nakorn Chiang Mai hospital: A retrospective study - Tuanjai Mahatumarat (2018)
© 2018, Medical Association of Thailand. All rights reserved. Background: Severity of acute pancreatitis varies from mild to severe. BISAP score is used for prediction of severity and mortality in acute pancreatitis and is a tool for triage patients for appropriate care. Objective: To determine etiology, severity and treatment outcomes of acute pancreatitis in Maharaj Nakorn Chiang Mai Hospital. Usage of the BISAP score to predict outcomes of treatment was also evaluated. Materials and Methods: Data pertinent to 115 patients with acute pancreatitis were retrospectively reviewed to define the incidence of severe acute pancreatitis, etiology of pancreatitis and treatment outcomes. Data regarding local complications, organ failure, length of hospital stay and death were also analyzed to evaluate the capability of the BISAP score for prediction of outcomes. Results: The major causes of acute pancreatitis were gallstones (43.5%) and alcohol use (36.5%). Twenty-one patients (18%)were classified as having severe acute pancreatitis. Overall mortality was 4.3% and rising to 24% in severe acute pancreatitis. The relationship between the development of severe acute pancreatitis with a BISAP score >3 (p<0.001) and mortality (p<0.001) was statistically significant. It was also associated with increased organ failure but not local complications. Conclusion: Etiologies, severity and outcomes of acute pancreatitis in this study were similar to previous studies. A BISAP score >3 was valuable in the prediction of severe acute pancreatitis and mortality.